# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime }-y = t^{2}-2 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 4 t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = t^{2}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = t
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 t y}{t^{2}+1} = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {4 t y}{4 t^{2}+1} = 4 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x +\frac {x y}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (t \right ) = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {3 t y}{t^{2}-4} = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {4 t y}{4 t^{2}-9} = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {9 x y}{9 x^{2}+49} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y \cot \left (x \right ) = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{y^{2}+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x = y
\] |
✓ |
✓ |
|
\[
{}y-\left (x +3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {3 x t^{2}}{-t^{3}+1}
\] |
✓ |
✓ |
|
\[
{}p^{\prime } = t^{3}+\frac {p}{t}
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+v = {\mathrm e}^{-s}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 4 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 t^{2} y = {\mathrm e}^{-t^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 t y = 2 t
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = 2 t \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{t}+1\right ) y^{\prime }+{\mathrm e}^{t} y = t
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+4\right ) y^{\prime }+2 t y = 2 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x+t +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{2 t}+2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} 4 & 0\le t <2 \\ 0 & 2\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 0 & 1\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 5 \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2-{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 27 t^{2}+9
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = 5 \cos \left (t \right )+2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = 8 \cos \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+10 y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 27 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 4+3 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 \cos \left (t \right )+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{2} = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = \cos \left (t \right ) t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{2}-\frac {y}{2 \sqrt {t}}+\left (2 t y-\sqrt {t}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {t}{\sqrt {t^{2}+y^{2}}}+\frac {y y^{\prime }}{\sqrt {t^{2}+y^{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (t y\right )+t \cos \left (t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sec \left (t \right )^{2}+2 t +\tan \left (t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t y^{2}+y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t -\sin \left (t \right ) y+\left (y^{6}+\cos \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (2 t \right )+\left (\sqrt {y}+\cos \left (2 t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (t y\right )+\frac {t y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t y}+\frac {t \,{\mathrm e}^{t y} y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2}-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-1+3 y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+2 t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {3 t^{2}}{y}-\frac {t^{3} y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}2 t +y^{3}+\left (3 t y^{2}+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {1}{y}+\left (\frac {t}{y^{2}}+3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+\left (t^{2}+y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{3}+\left (1+3 t^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )^{2}+t \sin \left (2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2}+3 y^{2}+6 t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t} \sin \left (y\right )+\left (1+{\mathrm e}^{t} \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2} y+3 y^{2}-1+\left (t^{3}+6 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-2 t y^{2} \sin \left (t^{2}\right )+2 y \cos \left (t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -y^{2} \sin \left (t y\right )+\left (\cos \left (t y\right )-t y \sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1-y^{2} \cos \left (t y\right )+\left (t y \cos \left (t y\right )+\sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}2 t \sin \left (y\right )-2 t y \sin \left (t^{2}\right )+\left (t^{2} \cos \left (y\right )+\cos \left (t^{2}\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (3+t \right ) \cos \left (y+t \right )+\sin \left (y+t \right )+\left (3+t \right ) \cos \left (y+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 t^{2} y \cos \left (t^{2}\right )-y \sin \left (t^{2}\right )}{t^{2}}+\frac {\left (2 t y+\sin \left (t^{2}\right )\right ) y^{\prime }}{t} = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {y^{2} {\mathrm e}^{\frac {y}{t}}}{t^{2}}+1+{\mathrm e}^{\frac {y}{t}} \left (1+\frac {y}{t}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \sin \left (\frac {y}{t}\right )-y \cos \left (\frac {y}{t}\right )+t \cos \left (\frac {y}{t}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{2}+2 t^{2} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+\frac {y}{t^{2}}-\frac {y^{\prime }}{t} = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+3 t^{2}+\left (t^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+5 t -y-\left (t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}-2 t y+\left (t \,{\mathrm e}^{y}-t^{2}\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}2 t y \,{\mathrm e}^{t^{2}}+2 t \,{\mathrm e}^{-y}+\left ({\mathrm e}^{t^{2}}-t^{2} {\mathrm e}^{-y}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-2 \sin \left (2 t \right )+\left (1+2 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right )^{2}-\sin \left (t \right )^{2}+y+\left (\sec \left (y\right ) \tan \left (y\right )+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{t^{2}+1}-y^{2}-2 t y y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {2 t}{t^{2}+1}+y+\left ({\mathrm e}^{y}+t \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}-2 x -y \cos \left (x y\right )+\left (2 y-x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-4 x^{3}+6 y \sin \left (6 x y\right )+\left (4 y^{3}+6 x \sin \left (6 x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y+t^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 \,{\mathrm e}^{t}+4 t \right )+3 \left ({\mathrm e}^{t}+t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (2 t -y \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+y^{2}-t^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|